Analisis Kinerja Keuangan Berdasarkan Rasio Profitabilitas PT Pertani (Persero) - Mangkona, Suriyanti; Asri, Dandi; Salim, Ahmad; Ma’ruf, Muhammad; Wahyuddin, Wahyuddin (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to determine & analyze financial performance based on profitability ratios at PT Pertani (Persero) Kab. Sidenreng Rappang. Data collection methods used in this research are observation, interview, and documentation methods. Types and sources of research data using quantitative data in the form of primary data and secondary data. This study uses profitability ratios with four indicators for calculating the value of financial ratios: (1) Gross Profit Margin (2) Net Profit Margin Earning Before Interest and Tax to Total Assets using profitability ratios, (3) Return On Assets (4) Return On Equity. The research results show that financial performance has not been efficient and effective, as seen from the 2018 Gross Profit Margin of 0.025%, 0.031% in 2019, and 0.021% in 2020. Net Profit Margin in 2018 was 0.014%, in 2019 it was -0.007%, and in 2020 it was -0.036%. Return On Assets in 2018 was 0.0026%, in 2019 it was -0.0015%, and in 2020 it was -0.0018%. Return On Equity in 2018 was 0.0025%, in 2019 it was -0.0016%, and in 2020 it was -0.0016%. PT. Agriculture (persero) Kab. Sidenreng Rappang must evaluate its current performance in utilizing assets and equity to maximize profit so that the company is able to make financial performance effective and efficient.